Carneiro Leão: considerations about the prospect of educational sociology - Rosilene de Lima; Maria Cristina Gomes Machado (Educação (Santa Maria. Online), 2015)
This article presents a description of some considerations about the prospect of Educational Sociology of Antônio Carneiro Leão (1887- 1966). It is considered and appropriated, at first reviewing some of this important bibliographic Brazilian intellectual, as well as we seek to explain some Carneiro Leão conceptions about the Educational Sociology, analyzing the author’s though about it. So, we worked as research sources the books: Foundations of Sociology (1963), which the first edition dates 1940, and “Sociology Vision of Brazil”, published in 1958. We believe that both publications give us referrals and subsidies for we can understand the Carneiro Leão conceptions about the Educational Sociology.